Analisis metode pembelajaran problem based learning untuk meningkatkan keterampilan berpikir kritis peserta didik - Putri, Kartika Amira; Arybasuki, Pradana Esa; Auliah, Siti; Az’zahrah, Siti Haniifah; Juniawati, Winda; Pedhu, Yoseph (Indonesian Institute for Counseling, Education and Theraphy, 2022)
Improving critical thinking skills has become the main focus in education in the current era, especially at the secondary school level. This research aims to analyze the application of the Problem-Based Learning (PBL) method in classical guidance services as an effort to improve the critical thinking skills of students. Through a literature study approach, journal articles, books and research related to PBL in the context of classical guidance services were compiled to evaluate the potential and challenges of this method. The analysis results show that PBL provides a solid framework for building students' critical thinking skills through in-depth and contextual problem solving experiences. This approach also allows for more active and collaborative interactions between students, supporting the development of analytical, evaluative, and synthetic thinking skills. However, challenges such as thorough material preparation, effective time management, and the teacher's role as facilitator remain a concern in implementing PBL in the context of classical guidance services. This research provides important insights for the development of learning strategies that are more oriented towards developing students' critical thinking skills.